Ornamental plant safety and weed control with indaziflam - Jatinder S Aulakh; Anthony Witcher; Vipan Kumar (Weed Technology)
Indaziflam was evaluated in Connecticut and Tennessee for weed control and safety of container-grown ornamental plants. Indaziflam was applied at 49, 98, or 196 g ha−1 to container-grown ornamental plants on an outdoor gravel pad and also applied preemergence or early postemergence to weeds in a greenhouse. Ornamental plants were treated twice annually in 2020 and 2021 in Connecticut, and in 2019 and 2020 in Tennessee, with approximately 6 wk between applications. Chinese pyramid juniper, common juniper, eastern hemlock, eastern white pine, and Norway spruce in Connecticut, and ‘Andorra Compacta’ creeping juniper and ‘Black Dragon’ Japanese cedar, ‘Blue Rug’ creeping juniper, and ‘Blue Pfitzer’ Chinese pyramid juniper in Tennessee were not injured with indaziflam regardless of the rate applied. Preemergence application of indaziflam reduced densities of creeping woodsorrel, hairy bittercress, giant foxtail, and large crabgrass by 72% to 100%, depending on the indaziflam rate applied, by 28 d after treatment (DAT). When applied early postemergence, indaziflam provided 97% to 99% control of creeping woodsorrel (1- to 2-leaf), fringed willowherb (4- to 6-leaf), hairy bittercress (cotyledon to 1-leaf), and mouse-ear chickweed (2- to 4-leaf) by 28 DAT. Compared with a nontreated control, the total fresh shoot biomass reduction was 86% to 100% and 78% to 100% following preemergence or postemergence applications. Indaziflam offers a new site of action with excellent safety and weed control in the tested ornamental plants.